Response Gene to Complement 32 promotes cell proliferation and tamoxifen resistance in breast cancer via elevated FoxM1 expression - Xinlei Li; Yan Liu; Zhiqian Wang; Xiaocui Bu; Yu Wang; Wei Zhang; Peng Zhao (PLoS ONE, 2025)
Despite the high sensitivity of estrogen receptor positive (ER+) breast cancer to endocrine therapy, many patients have primary resistance or develop resistance to endocrine therapies. Acquired resistance to endocrine therapy is a great challenge in the treatment of ER+ breast cancer patient. Here we showed that Response Gene to Complement (RGC)-32 expression is higher in breast cancer than paired normal tissues, which was a poor predictive factor. RGC-32 overexpression resulted in tamoxifen resistance, whereas knockdown of RGC-32 in tamoxifen-resistant cells restored tamoxifen sensitivity. Tamoxifen resistance mediated by RGC-32 was shown to be partially dependent on FoxM1 expression. Mechanistically, RGC-32 could activated PI3K signaling pathway, and then enhanced estrogen receptor alpha (ERα) activity. ERα activation is essential for RGC-32-mediated the expression of FoxM1. These data support that targeting RGC-32 could effectively mitigate cancer progression and tamoxifen resistance, offering a complementary therapeutic approach to reduce acquired endocrine resistance.